A novel current-control method for three-phase PWM AC DC voltage-source converters - Kömürcügil, H; Kükrer, O (IEEE-Inst Electrical Electronics Engineers Inc, 1999)
This paper presents a novel current-control-based control strategy, obtained in stationary frame, for a three-phase pulsewidth-modulated ac/dc voltage-source converter. In this control strategy, an error voltage is produced from the comparison of the output de voltage,vith a de reference voltage. This error voltage is then utilized by a proportional plus integral controller to generate a command signal for the input line current amplitude and is automatically controlled to the desired value. Therefore, there is no need to measure the input line currents. Stability analysis of the closed-loop system is made, and the stability region for proportional and integral gains which makes the operating point stable is also found, The resulting closed-loop system not only exhibits good transient response, but also provides sinusoidal line currents and unity power factor, both in the rectifying and regenerating modes. Experimental results are presented and compared with simulations.
Keywords: current-control methods; space-vector pulse-width modulation; three-phase ac dc converters